IDENTIFIKASI MANFAAT EKONOMI & SOSIAL CAR FREE DAY SURODINAWAN BAGI PEDAGANG KAKI LIMA - Nurdiana Fitri Isnaini; Yuliasnita Verlandes; Aulia Nur Sayidah (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2022)
exhaust emissions, makes it a special gift for street vendors to carry out activities to fulfill the needs of the perpetrators. Street vendors choose places that are visited by many people, such as shop fronts and on the edge of roads, parks and markets, without permission from the government to sell their wares. The presence of activities in open spaces is a potential market that is always approached by economic actors, including street vendors. With the existence of CFD, it is necessary to see how far the benefits received by business actors, especially street vendors, because this is what determines the sustainability of their business which is very dependent on human crowds. This benefit is seen from two perspectives, namely from an economic and social perspective. The identification of the benefits of CFD for street vendors uses a qualitative approach with data collection methods using several techniques, namely in-depth interviews, participatory observation and documentation. Data collection in this study was carried out through three paths, namely reducing data, presenting data and drawing conclusions. By interviewing several street vendors in the CFD area, information was obtained that the economic impact for traders was quite good, by selling in the CFD area an increase in income of 30% - 40%, considering that during the pandemic the Surodinawan CFD area was still only allowed to be active again, new sellers and visitors allowed to come under the supervision of the Pamogpraja police of Mojokerto City. Social interactions between traders have a positive social impact, they communicate with each other, support each other that the pandemic must be passed with an unyielding spirit. After all, life must continue, it is not difficult to be alone, must remain excited for the sake of family members at home who are waiting with prayers.